Neue Sachlichkeit and Schulhoff ’s Improvisations: Paper from the conference: Neue Sachlichkeit, Political Music, or Vernacular Avant-Garde? Hanns Eisler and his Contemporaries - Wilson, Andrew (Danish Yearbook of Musicology, 2019)
Sami Dva (1933), a rare testimony of Erwin Schulhoff ’s jazz orientated piano duos, and Optimistische Komposition (1936), a transcription of one of his solo extemporizations, are evidence of the Czech musician’s skills in improvised music. These two examples also offer a unique opportunity to discuss how certain forms of improvised music might relate to a broad definition of musical Neue Sachlichkeit.